Evaluasi User Experience pada Game Mobile Legend menggunakan Cognitive Walkthrough - Drajat Khoirul Muslim; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Video games that are played online require a gaming device to be linked to the internet in order to function. Online games that may be played on a mobile device are among the most accessible. In digital games, the display—also known as the game interface—allows players to interact with the game. The interface of the game contains every sign, text, image, and hint. The developer must assess the produced interface in order to obtain a nice interface. Cognitive walkthrough is one of the analytical techniques that may be used to assess the usability of the user interface. Three versions of Cognitive Walkthrough are available The cognitive idea that the individual doing the evaluation must possess is highlighted in the first version. Because it is extremely complicated and time-consuming, the second version can be viewed as a failure. Preparation, analysis, and follow-up are the three stages in the third iteration of Cognitive Walkthrough. Both of the respondents—two individuals—had never played the mobile phone game. The respondents' findings will then be tabulated and presented in a table with an explanation to help with a more in-depth understanding. The responses included individuals in elementary school, junior high school, high school, college, and even those who were already employed.